Self-adaptive attribute weighting for Naive Bayes classification. Issue 3 (15th February 2015) - Wu, Jia; Pan, Shirui; Zhu, Xingquan; Cai, Zhihua; Zhang, Peng; Zhang, Chengqi
Highlights Self-adaptive attribute weighting for Naive Bayes classification. Using Artificial Immune Systems (AIS) for attribute weighting. Seamlessly integrating learning objective and AIS affinity function for attribute weighting. Experiments on 42 real-world datasets demonstrating superb performance gain.